Dividend Policy: Analyzed from Stock Prices and Firm Size in Indonesia's Manufacturing Sector - Wufron, Wufron; Silva Siti Parwati, Neng; Alam Hamdani, Nizar; Sri Utami, Wulan (KnE Social Sciences, 2023)
The purpose of this study was to examine the effect of stock prices and firm size on dividend policy in manufacturing companies in Indonesia. In this quantitative researchinferential statistical analysis was used to test hypotheses. Based on certain criterias, purposive sampling technique was used. The data were taken from the company’s financial statements from 2018 to 2021. The data were analyzed using multiple regression analysis in order to test the research model and the influence between variables. The results showed that the stock price and firm size on dividend policy is a fit research model. Stock prices had a positive effect on dividend policy, whereas firm size had a negative effect on dividend policy. Stock prices had a significant effect on dividend policy,while firm size had a significant effect on dividend policy. The findings in this study showed that the assets of manufacturing companies in Indonesia during 2018 to 2021 experienced fluctuations, this will directly affect the welfare of investors. The importance of this research is to jointly maintain the existence of all manufacturing companies in Indonesia because companies engaged in the manufacturing sector are very influential in the economic sector. Keywords: company size, dividend policy, manufacturing sector company, stock price